Rare Manifestation of COVID-19 Resulting in Coronary Artery Vasculitis - Ahmed Hassaan Qavi; Soban Ahmad; Neeraj N. Shah; Rony Shammas (Case Reports in Cardiology)
We present the case of a 59-year-old African American female with end-stage renal disease (ESRD) who presented to the emergency department with chest discomfort. She had a coronary angiogram six months ago that showed no occlusive epicardial coronary artery disease. She had elevated troponin I levels and new regional wall motion abnormalities on echocardiogram. Her SARS-CoV-2 returned positive. After a multidisciplinary team approach, she underwent another coronary angiogram that showed new severe multivessel ostial lesions and a left main coronary artery aneurysm. COVID-19-related coronary artery vasculitis was suspected based on her clinical presentation, angiogram findings, and negative autoimmune workup. The patient underwent successful coronary artery bypass grafting and recovered without complications.